A conceptual review of organisational learning orientation as an antecedent to knowledge transfer during an ERP implementation - Chagan Momade Aly, Shareen (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MPhil (Information Science))--University of Stellenbosch, 2007.